Guidelines for prevention of febrile neutropenia. - Barroso, Sérgio (2008)
Neutropenia and febrile neutropenia are common consequences of some cytotoxic chemotherapy regimens. This situation leads to modifications of the therapeutic regimen, conducting to either dose reduction or cycle delays. Granulocyte colony stimulating factors are commonly used to minimize chemotherapy cytotoxic effect on the granulocytic series. The objective of this study is to assess the available evidence in what concerns the efficacy and safety of granulocyte colony stimulating factors, in several settings of their use. An extensive bibliographic review was performed, including clinical trials, observational studies, systematic reviews, and international guidelines for neutropenia prophylaxis, which aims to establish recommendations on their use, in adequacy to the National reality.